Mathematics teachers' enactment of cognitively demanding tasks and students' perception of racial differences in opportunity. Issue 3 (3rd July 2019) - Munter, Charles; Haines, Cara
ABSTRACT: This study examined whether secondary students in an urban school district perceived racial differences in opportunity to be successful in mathematics, whether those perceptions differed between students of color and white students, and the relation of those perceptions to teachers' choice and implementation of mathematical tasks. The results of multi-level regression models based on student survey and teacher observation data revealed two primary findings: (a) students of color were more likely to perceive opportunity differences than were white students; and (b) this difference was greater in classrooms in which teachers attempted to use cognitively demanding tasks but allowed the cognitive demand to decline during the lesson. Implications for both future research and mathematics teacher education are discussed.